Quantum-dot-based biosensor for simultaneous detection of biomarker and therapeutic drug : first steps toward an assay for quantitative pharmacology - Yang, Chi (2013)
Quantitative pharmacology (QP) is often used to study the recommended dose of a drug. Using colorectal cancer as a model, the relationship between exposure (cetuximab, C225, therapeutic drug of colorectal cancer) and the biomarker response (carcinoembryonic antigen, CEA, biomarker of colorectal cancer) is the core for the QP of C225. Thus, simultaneous detection of CEA and C225 is the first step towards an assay for the QP of C225. We developed a quantum dot (QD)-based multi-analyte biosensor for the simultaneous determination of CEA and the corresponding therapeutic drug C225. The assay is based on the competition between a quantum-dots-labeled glycans and target glycans using lectins as the recognition element. The dual-analytic biosensor detected CEA and C225 in the range from 1 ng mL−1 to 400 μg mL−1 by stripping voltammetry. The biosensor developed here for the simultaneous detection of the biomarkers and therapeutic drugs is expected to develop as a potential technique for quantitative pharmacology.